2010
DOI: 10.1111/j.1745-9125.2010.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenility and Punishment: Sentencing Juveniles in Adult Criminal Court*

Abstract: The study outlined in this article addressed a key limitation of prior research on the punishment of juveniles transferred to adult court by employing propensity score matching techniques to create more comparable samples of juvenile and young adult offenders. Using recent data from the Maryland State Commission on Criminal Sentencing Policy, it tested competing theoretical propositions about the salience of juvenile status in adult court. Findings indicate that even after rigorous statistical matching procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 63 publications
4
64
2
Order By: Relevance
“…Paternoster and Brame (2008) recently applied this method to assess offender race/victim race disparity in death penalty sentences in Maryland. Kurlychek and Johnson (2010) recently used propensity scoring methods to study the sentencing of juveniles in adult court. Given critiques of traditional regression methods in connection with issues of selection and omitted variable bias, we may see increased use of propensity scoring methods to compare sentencing outcomes of different kinds of cases and offenders.…”
Section: New Methodological Extensionsmentioning
confidence: 99%
“…Paternoster and Brame (2008) recently applied this method to assess offender race/victim race disparity in death penalty sentences in Maryland. Kurlychek and Johnson (2010) recently used propensity scoring methods to study the sentencing of juveniles in adult court. Given critiques of traditional regression methods in connection with issues of selection and omitted variable bias, we may see increased use of propensity scoring methods to compare sentencing outcomes of different kinds of cases and offenders.…”
Section: New Methodological Extensionsmentioning
confidence: 99%
“…Berk et al, 2005). Some recent research that focuses on the role of juvenile waivers to adult courts provides a nice example how propensity score matching can enhance the capacity to make group comparisons in sentencing research (Kurlychek & Johnson, 2010), but I am not aware of any research that has supplemented the typical regression-based approach with such methods. It would be refreshing to see the modal approach to studying race and sentencing enhanced by adopting alternative estimation procedures for identifying group differences.…”
Section: Enhancing Research On Detecting Racial Disparitiesmentioning
confidence: 98%
“…First, our results indicated that waived individuals are incarcerated for a larger proportion of time during the time frame when we assessed aggregate earnings. Although it is possible that removal from the community during this time frame is linked with the initial petition to court and harsher punishments for waived offenders compared with similarly situated counterparts (see Kurlychek and Johnson, , ), it is also possible that removal from the community 6 and 7 years after the initial offense is a result of newly incurred punishments associated with increased rates of offending after waiver as the findings from some research suggest that waiver has a criminogenic effect at least among some offenders (Loughran et al., ; for a review see Zane, Welsh, and Mears, ). Either way, removal from the community in and of itself is a barrier to legal employment and stymies income generation.…”
Section: Discussionmentioning
confidence: 99%